(3GdcJGH GdYLjH aj GdgjFIs - (3CHh LYaQ GdHWQhZj,J (B581 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg Whd Gddg YeQc jG CNj aGeG GdZQV ggfG HYO cKjQg GdMeO ddg JYGdi Cf CNHQc eGdGM dHGdi hGhbac Ydi NGUg GdSQ ef TF YRjR MUd di s
(3BNQgG (B:s
(3hdjcf dc GdHbGA GdEdgi GdCOhe hGdYjT GdCQV GdCcQe hGdSdGe Ydjc s
(3ajgG HYV GdQShe GdgfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B866 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B96 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3302) s
Keywords: (3Gdadcs